ANALYSIS OF QUESTIONS FROM THE DESCRIPTORS D16, D17, D18, D20, D27 OF MATHEMATICS OF THE 9TH GRADE OF ELEMENTARY SCHOOL OF THE PERNAMBUCO BASIC EDUCATION EVALUATION SYSTEM (SAEPE) FROM THE 2015 TO 2019 EDITIONS - Santana, Patrícia (Revista Gênero e Interdisciplinaridade, 2023)
The purpose of this work is to raise new study possibilities and analyze questions that are applied in the external evaluation of the Pernambuco Basic Education Evaluation System, the SAEPE. This does not measure the student’s ability, but the development of teaching with basic contents of Portuguese and Mathematics, so that an analysis of the general context can be carried out in order to improve their educational sequence in state public schools. Therefore, there is a reference matrix that was created precisely as a basis for these assessments. The 9th grade of elementary school, focus of this research, is composed of 38 descriptors. An analysis of the questions that appeared in the SAEPE of the descriptors D16, D17, D18, D20, D27 between the years 2015-2019 will be carried out, so that a reflection of the levels launched and that are tested with each application that usually occurs in the month of November, on the last Wednesday of the month and which has been applied since the year 2000. It is hoped that such analyzes can serve as a basis for improving the way teachers usually prepare their students and even contribute to an improvement in the tests of the SAEPE.